Public service motivation and job performance: evidence from the federal sector - Alonso, Pablo; Lewis, Gregory B. (2001)
Perry and Wise (1990) argued that people with high public service motivation (PSM) are more likely than others to choose government jobs, to perform better on the job, and to respond more to nonutilitarian incentives once in government. Using multiple regression and logit analyses on responses by 35,000 federal, white-collar employees to the 1991 Survey of Federal Employees and the 1996 Merit Principles Survey, this article tests the link between PSM and job performance in the federal service. There is mixed evidence on whether PSM positively affected grades and performance ratings, clearer evidence that employees who expected to receive a material reward for exceptional performance attained higher grades a nd performance ratings, and no evidence that the link between material rewards and performance mattered any less to those with high PSM. - Reproduced.
Keywords: Motivation; Civil service